Quality by Design-based Formulation and Evaluation of Fast Dissolving Tablet of Aspirin - Desai, Dr. S. R. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The focus of the current study was to develop fast dissolving tablet (FDT) of aspirin using quality by design (QbD) approach. QbD was applied for better understanding the process and to enhance design space, using quality target product profile, critical quality attributes, and risk assessment. The aim of the project is to achieve early onset of aspirin by FDT. Materials and Methods: FDT of aspirin was developed by 32 factorial using Box–Behnken design. In factorial design we have selected two variables povidone and crospovidone at three levels. The response surface plots were generated. Ultraviolet (UV), Fourier-transform infrared, differential scanning calorimeter (DSC), and X-ray diffraction (XRD) analysis have been done for pre-formulation and post-formulation evaluations. The tablets were prepared by direct compression method. Results and Discussions: The λmax was confirmed at 275 nm by UV spectroscopy. In compatibility study IR, it was observed that the drug was in pure form and there were no major interactions with other polymers. DSC and XRD studies revealed that the drug was in crystalline form showing sharp peaks. The in vitro dissolution study revealed that the batch F7 is best among nine batches been prepared. It was stable at 25°C ± 2°C/60% ± 5% RH and 40°C ± 2°C/70% ± 5% RH for 90 days. Conclusion: The study indicates that FDT of aspirin using QbD approach was successfully developed.